Proceedings of the First International Conference on Islamic History and Civilization, ICON-ISHIC 2020, 14 October, Semarang, I 2021
DOI: 10.4108/eai.14-10-2020.2303861
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mindfulness and Digital Detox to Adolescent Nomophobia

Abstract: Nomophobia is an important study in the digital era. Nomophobia is related to an individual's anxiety when they are away from gadgets and has an impact on daily activities. This study aims to empirically examine the effects of mindfulness and digital detox on nomophobia in adolescents. The hypothesis proposed in this study is that there is an effect of mindfulness and digital detox on nomophobia in adolescents. The subjects of this study consisted of 40 people. The analytical methods used is the paired sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…One of research explained that mindfulness interventions and digital detoxification can reduce the tendency of nomophobia (fear of not being able to access cellphones) in adolescents [13]. This is in accordance with the five participants interviewed by researchers who also stated that the use of social media without self-control and individual expectations due to the latest uploads by friends on social media causes anxiety.…”
Section: Icopsysupporting
confidence: 60%
“…One of research explained that mindfulness interventions and digital detoxification can reduce the tendency of nomophobia (fear of not being able to access cellphones) in adolescents [13]. This is in accordance with the five participants interviewed by researchers who also stated that the use of social media without self-control and individual expectations due to the latest uploads by friends on social media causes anxiety.…”
Section: Icopsysupporting
confidence: 60%
“…Mindfulness encourages individuals to observe all emotions from a detached perspective. Since the 1970s, mindfulness has been used in therapeutic interventions for common psychological problems such as stress, worry, anxiety, and depression (Abedini & Joibari, 2023;Aini et al, 2021;Allen et al, 2021). The mindfulness-based stress reduction program has shown great efficacy in terms of adaptability and has been beneficial for primary prevention in health or similar sets, achieving the best results in patients with stress symptoms results of the repeated measures analysis of variance along with the post-hoc tests indicated that there were no significant differences between the post-test and follow-up stages for stress and rumination variables (P>0.05); hence, the results were stable.…”
Section: Methodsmentioning
confidence: 99%